2017
DOI: 10.1007/s11999-017-5278-9
|View full text |Cite
|
Sign up to set email alerts
|

Hamstring Autograft versus Patellar Tendon Autograft for ACL Reconstruction: Is There a Difference in Graft Failure Rate? A Meta-analysis of 47,613 Patients

Abstract: Level III, therapeutic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
252
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 296 publications
(265 citation statements)
references
References 51 publications
6
252
1
6
Order By: Relevance
“…14 Similar advantages of BTB have not been demonstrated in the meta-analyses or systematic reviews comparing the outcomes of BTB and hamstring tendon autografts. 39,40 The potential advantage of a combined ACLþALL graft has been attributed to load sharing of the ALL 41 with the reconstructed ACL. Furthermore, it has also been reported that at lateral exploration of apparently isolated acute ACL injured knees, injury to the anterolateral structure is identified in approximately 90% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…14 Similar advantages of BTB have not been demonstrated in the meta-analyses or systematic reviews comparing the outcomes of BTB and hamstring tendon autografts. 39,40 The potential advantage of a combined ACLþALL graft has been attributed to load sharing of the ALL 41 with the reconstructed ACL. Furthermore, it has also been reported that at lateral exploration of apparently isolated acute ACL injured knees, injury to the anterolateral structure is identified in approximately 90% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent randomised controlled trial with large population comparing BPTB, SB and DB hamstring tendon grafts showed that more traumatic reinjuries occurred with SB and DB hamstring grafts compared with BPTB. However, no recent systematic reviews or meta-analyses of randomised or prospective studies showed any difference in the revision rate between hamstrings and BPTB grafts,2 3 6 except one most recent meta-analysis showing that hamstring tendon graft failed at a higher rate than BPTB graft 4. One large limitation of this study is, however, that most of the patients included in this study came from the Scandinavian registry study with the lowest Modified Coleman Methodology Score and those results factor heavily into the results (79.1%).…”
Section: Current State Of the Art: Graft Selectionmentioning
confidence: 99%
“…Several studies have shown that hamstring tendons are associated with higher retear rates, decreased knee flexion strength, and increased infection than both patellar tendon and quadriceps tendon grafts. [46][47][48][49][50][51] Consequently, in the young patients, active Service member, autograft reconstruction with hamstring tendons is often a secondary graft choice in the most high-risk patient populations. Patellar tendon autograft has become the preferred method of ACL reconstruction by military orthopaedic surgeons as it has repeatedly been shown to have the most secure fixation with low failure rates and high patient reported outcomes.…”
Section: Graft Considerationsmentioning
confidence: 99%